Regulation of ferroptosis in osteoarthritis and osteoarthritic chondrocytes by typical MicroRNAs in chondrocytes - Yu, Qingyuan; Xiao, Yanan; Guan, Mengqi; Zhou, Guohui; Zhang, Xianshuai; Yu, Jianan; Han, Mingze; Yang, Wei; Wang, Yan; Li, Zhenhua (Frontiers in Medicine, 2024)
Osteoarthritis (OA) is a progressive degenerative disorder impacting bones and joints, worsened by chronic inflammation, immune dysregulation, mechanical stress, metabolic disturbances, and various other contributing factors. The complex interplay of cartilage damage, loss, and impaired repair mechanisms remains a critical and formidable aspect of OA pathogenesis. At the genetic level, multiple genes have been implicated in the modulation of chondrocyte metabolism, displaying both promotive and inhibitory roles. Recent research has increasingly focused on the influence of non-coding RNAs in the regulation of distinct cell types within bone tissue in OA. In particular, an expanding body of evidence highlights the regulatory roles of microRNAs in OA chondrocytes. This review aims to consolidate the most relevant microRNAs associated with OA chondrocytes, as identified in recent studies, and to elucidate their involvement in chondrocyte metabolic processes and ferroptosis. Furthermore, this study explores the complex regulatory interactions between long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) in OA, with an emphasis on microRNA-mediated mechanisms. Finally, critical gaps in the current research are identified, offering strategic insights to advance the understanding of OA pathophysiology and guide therapeutic developments in this field.